Business Information Systems Workshops : BIS 2019 International Workshops, Seville, Spain, June 26-28, 2019, Revised Papers /: BIS 2019 International Workshops, Seville, Spain, June 26-28, 2019, Revised Papers. (2019) - Unknown
No abstract available